Dependence of the Enthalpy of Formation of Phenols on Molecular Structure – Semiempirical Study. (14th September 2021) - Marković, Svetlana; Redžepović, Izudin; Furtula, Boris
Abstract: The ability of three semiempirical methods (PM3, PM5, and PM7) in reproducing the enthalpy of formation (Δf H °) of polycyclic aromatic phenols (PAPs) was tested by comparing experimental and calculated values for 33 compounds. In addition, the results from the semiempirical methods were compared to those obtained from the suitable isodesmic reactions, performed using the B3LYP–D3 and M06–2X functionals in combination with the 6-311 + G(d, p) basis set. With an average absolute error less than 10 kJ mol −1, all five methodologies yielded mutually comparable results. Considering low computational cost of semiempirical methods, the influence of structural features on Δf H ° of PAPs was investigated using the PM5 and PM7 methods. It was found that the greatest influence on Δf H ° has the size of the molecules, while the effects of other properties, i.e., the position of the OH group, number of bay regions, and molecular branching are weaker. The influence of the OH group position decreases with its moving away from molecular ends, and eventually becomes insignificant. As branching and the number of bay regions are mutually dependent and respective molecules are often nonplanar, it is difficult to examine individual contributions of these two structural features. In general, Δf H ° decreases with increasing number of bay regions and molecular branching.